Functioning of the quasi-labor market under socialism: Clash between ideology and reality - Lucie Coufalová; Libor Žídek (DANUBE: Law, Economics and Social Issues Review, 2019)
Based on the interviews with that time managers, the paper aims to find out whether ideology affected the dealing with labor force in the last two decades of the socialist regime in Czechoslovakia. Technically, the labor market was balanced and characterized by zero unemployment and low and highly equalized wages. However, actually, there was a permanent imbalance with the lasting dominance of demand over supply and overemployment. Increasing wages was, due to ideological and formal settings of the system nearly impossible, and thus the economic agents tried to find alternative "solutions" to this imbalance. This situation led to lowmotivation of the labor force and consequently to low productivity. The positive side was represented by relatively good relationships among the employees. We demonstrate on the interviews that in the clash between ideology and the market forces, the former was stronger and in fact prevented efficient functioning of the labor market.
Keywords: 330; Labor Market; Balance; Shortage Economy; Motivation; Czechoslovakia